A heurística de Pólya e a resolução de problemas de trigonometria - Pinheiro, Luizalba Santos e Souza (2017)
In our dissertation, we study and interpret George Pólya’s ideas on solving problems, basing, fundamentally, on his paradigmatic opus entitled How to solve it. We also take as sources some works resulting from researches on the application of the heuristic method in solving mathematical problems. We applied these ideas to solve a set of trigonometric problems, most of them whit above-average difficulty. We have included problems in proving identities, solving equations, transforming trigonometric expressions and calculating extremes. In a sufficient number of these problems, we include indications for using the heuristic method in the classroom. The work is aimed at high school teachers and students motivated by the resolution of trigonometric problems.